Oesophageal cancer treatment patterns, timeliness of care and outcomes in the Loddon Mallee region of Victoria: A retrospective cohort study. Issue 2 (26th February 2021) - Conway, Paul; Leach, Michael; Tejani, Neetu; Robinson, Amanda; Shethia, Yachna; Solo, Ilana
Abstract: Introduction: Few studies have investigated oesophageal cancer care in regional areas. This study aimed to describe treatment patterns for oesophageal cancer in a regional area, and to identify factors associated with radiotherapy utilisation, timeliness of care, and death. Methods: In a retrospective cohort study, medical records were reviewed to source data on all patients diagnosed with and/or treated for oesophageal cancer at two regional Victorian hospitals over July 2015–June 2018. Cox proportional hazards regression was employed to identify factors associated with time from diagnosis to death while binary logistic regression was used to identify factors associated with radiotherapy utilisation and treatment within 28 days of diagnosis – a time frame derived from the relevant optimal care pathway. Results: Of 95 patients, 72% had radiotherapy, 32% received any treatment within 28 days, and 78% died over a median time of nine months. Odds of not receiving radiotherapy were decreased (odds ratio [OR] = 0.26, 95% confidence interval [CI] = 0.08–0.87) for histology other than adenocarcinoma. Odds of timely care were increased for any palliative radiotherapy (OR = 3.47, 95% CI = 1.15–10.5) and decreased for older age (OR = 0.95, 95% CI = 0.91.0.999). Hazard of death was elevated for stage IV disease (hazard ratio [HR] = 2.73, 95% CI = 1.64–4.54) and reduced for radical intent (HR = 0.27, 95% CI = 0.15–0.48). Conclusion: Nearly three‐quarters of regional oesophageal cancer patients had radiotherapy while approximately one‐third received any treatment within the recommended 28 days. Any palliative radiotherapy and younger age were associated with timely treatment. Future studies could further investigate factors related to timely oesophageal cancer care.